Early Detection of Atherosclerotic Changes in Diabetic Patients - Dey, Prashanta Prasum; Paul, S (KYAMC Journal, 2013)
DOI: http://dx.doi.org/10.3329/kyamcj.v1i1.13304 KYAMC Journal Vol.1(1) July 2010, 27-29